Exploring Ice-Breaking in Natural and Social Sciences Learning: Case from an Indonesian Elementary School - Arianti, Riska Octavia; Reffiane, Fine; Sukamto, Sukamto (Mimbar Sekolah Dasar, 2025)
In the context of elementary school education, it is essential to apply teaching methods that maintain students’ engagement and interest. One effective method is ice-breaking, designed to create a pleasant and comfortable learning atmosphere by reducing initial tension. This study aimed to analyze the implementation of ice-breaking activities in the teaching of Natural and Social Sciences (NSS) for Grade 3 students at a public elementary school in Central Java, and its impact on student engagement and learning outcomes. The research adopted a qualitative case study approach, utilizing classroom observations and teacher interviews. The findings indicate that the application of ice-breaking activities significantly increased students’ interest and enjoyment in NSS lessons, improved comprehension of the material, and enhanced confidence in answering questions. Prior to the intervention, students showed relatively low engagement and interest in learning NSS. After the intervention, observations and interviews indicated that students became more engaged and expressed greater enjoyment in the learning process. Despite these benefits, challenges such as limited instructional time and initial resistance to new strategies were observed. To address these issues, concise and relevant activity planning and professional development for teachers are recommended. These results imply that the integration of ice-breaking activities can meaningfully improve the learning experience at the primary level.